A Performance Analysis of System Rollback Techniques - Sousa, Antônio Drumond Cota de; Freitas, Henrique Cota de (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2025)
System restorations are crucial for maintaining operational continuity, yet the lack of comparative performance data makes selecting the right rollback tool a significant challenge. This paper addresses this gap by conducting a quantitative performance analysis of four popular techniques: NixOS Generations, Snapper, Timeshift (in RSYNC mode), and Windows System Restore. We evaluated each tool based on two key metrics: rollback duration and snapshot storage size, using a controlled virtualized environment. Our results reveal significant performance disparities, with rollback speeds differing by up to a factor of four, indicating that filesystem-integrated, copy-on-write tools are demonstrably more efficient for performance-critical applications.